Manajemen Penanggulangan Banjir Di Kelurahan Paccerakkang Kota Makassar - Muh Wahyudi; Ruskin Azikin; Samsir Rahim (Kolaborasi : Jurnal Administrasi Publik, 2019)
This research aims to know the management of flood prevention in the Paccerakkang of district office and how to know the factors that effect the management. This research is categorized in qualitative research and type of research is phenomenology. The number of the informants are 9 people which is chosen purposively. The data collection techniques are observation, documentation, and depth interview. The result of the research shows that the implementation of management of flood prevention has done quite good, but there is still more needs to be repaired. The community is aware that the importance of participation and cooperation in the management of flood. The main factors that effect the management is chairman , employes behaviour , work groups behaviour and external factors.